Nelly Richard, Crítica de la memoria (Altre Modernità, 2023)
Nelly Richard, Crítica de la memoria(Santiago de Chile, Ediciones Universidad Diego Portales, 2010, 271 pp. ISBN 978-956-314-106-1) por Giuseppe Calì